Sublingual misoprostol versus standard surgical care for treatment of incomplete abortion in five sub-Saharan African countries (2012)
Background: In low-resource settings, where abortion is highly restricted and self-induced abortions are common, access to post-abortion care (PAC) services, especially treatment of incomplete terminations, is a priority. Standard post-abortion care has involved surgical intervention but can be hard to access in these areas. Misoprostol provides an alternative to surgical intervention that could increase access to abortion care. We sought to gather additional evidence regarding the efficacy of 400 mcg of sublingual misoprostol vs. standard surgical care for treatment of incomplete abortion in the environments where need for economical non-surgical treatments may be most useful. Methods: A total of 860 women received either sublingual misoprostol or standard surgical care for treatment of incomplete abortion in a multi-site randomized trial. Women with confirmed incomplete abortion, defined as past or present history of vaginal bleeding during pregnancy and an open cervical os. were eligible to participate. Participants returned for follow-up one week later to confirm clinical status. If abortion was incomplete at that time, women were offered an additional follow-up visit or immediate surgical evacuation. Results: Both misoprostol and surgical evacuation are highly effective treatments for incomplete abortion (misoprostol: 94.4%, surgical: 100.0%). Misoprostol treatment resulted in a somewhat lower chance of success than standard surgical practice (RR = 0.90; 95% Cl: 0.89-0.92). Both tolerability of side effects and women's satisfaction were similar in the two study arms. Conclusion: Misoprostol, much easier to provide than surgery in low-resource environments, can be used safely, successfully, and satisfactorily for treatment of incomplete abortion. Focus should shift to program implementation, including task-shifting the provision of post-abortion care to mid- and low- level providers, training and assurance of drug availability.